Exploring the therapeutic potential of targeting polycomb repressive complex 2 in lung cancer - Gao, Min; Li, Yongwen; Cao, Peijun; Liu, Hongyu; Chen, Jun; Kang, Shirong (Frontiers in Oncology, 2023)
The pathogenesis of lung cancer (LC) is a multifaceted process that is influenced by a variety of factors. Alongside genetic mutations and environmental influences, there is increasing evidence that epigenetic mechanisms play a significant role in the development and progression of LC. The Polycomb repressive complex 2 (PRC2), composed of EZH1/2, SUZ12, and EED, is an epigenetic silencer that controls the expression of target genes and is crucial for cell identity in multicellular organisms. Abnormal expression of PRC2 has been shown to contribute to the progression of LC through several pathways. Although targeted inhibition of EZH2 has demonstrated potential in delaying the progression of LC and improving chemotherapy sensitivity, the effectiveness of enzymatic inhibitors of PRC2 in LC is limited, and a more comprehensive understanding of PRC2's role is necessary. This paper reviews the core subunits of PRC2 and their interactions, and outlines the mechanisms of aberrant PRC2 expression in cancer and its role in tumor immunity. We also summarize the important role of PRC2 in regulating biological behaviors such as epithelial mesenchymal transition, invasive metastasis, apoptosis, cell cycle regulation, autophagy, and PRC2mediated resistance to LC chemotherapeutic agents in LC cells. Lastly, we explored the latest breakthroughs in the research and evaluation of medications that target PRC2, as well as the latest findings from clinical studies investigating the efficacy of these drugs in the treatment of various human cancers.